IMF Committee on Balance of Payments Statistics : Annual Report 2005. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2006)
This is the annual report of the IMF Committee on Balance of Payments Statistics, which was established in 1992 to (i) oversee implementation of the recommendations contained in the reports of two IMF working parties that investigated the principal sources of discrepancy in global balance of payments statistics published by the IMF, (ii) advise the IMF on methodological and compilation issues in the context of balance of payments and international investment position statistics, and (iii) foster greater coordination of data collection among countries. This report includes an Executive Summary, an overview of statistical discrepancies in the global balance of payments statistics published by the IMF's Statistics Department, and a discussion of the Committee's work program during 2005 and proposed work program for 2006.